High Smad7 marks inflammation in patients with chronic pouchitis - Maresca, Claudia; Iannucci, Andrea; Colella, Marco; Frascatani, Rachele; Laudisi, Federica; Lolli, Elisabetta; Marafini, Irene; Zorzi, Francesca; Salvatori, Silvia; Monteleone, Ivan; Bellinvia, Salvatore; Stolfi, Carmine; et al. (Frontiers in Immunology, 2025)
Background and aimPatients with ulcerative colitis (UC) undergoing colectomy with ileal-anal pouch anastomosis can develop chronic pouchitis (CP). Since treatment options are very limited for patients with CP, identification of factors/mechanisms that amplify the CP-associated inflammatory response could help develop novel treatments. We here assessed the expression of Smad7, an inhibitor of TGF-β1 signaling and positive regulator of gut inflammation, in CP.MethodsMucosal samples were taken from the inflamed pouch of patients with CP, whose activity was evaluated by the modified Pouchitis Disease Activity Index (mPDAI). Controls included mucosal biopsy samples taken from the uninflamed pouch of patients with a history of CP and ileal samples taken from normal/inflamed pre-pouch of patients with CP and normal controls. Smad7 expression was assessed by Western blotting and immunofluorescence, and the Smad7-expressing lamina propria mononuclear cells (LPMCs) were evaluated by flow cytometry. Mucosal samples taken from the inflamed pouch of CP patients were cultured with a Smad7 antisense (AS) or sense oligonucleotide and TNF-α and interleukin (IL)-8 were evaluated by real-time PCR and ELISA.ResultsEnhanced Smad7 expression was seen in the inflamed pouch of patients with CP compared to the normal or inflamed ileum of the same patients and the uninflamed pouch of patients with no pouchitis and normal controls. In the inflamed mucosa of patients with CP, Smad7 was more abundant in LPMCs, mainly in T lymphocytes. Knockdown of Smad7 in ex vivo mucosal explants taken from CP patients was associated with a reduction in TNF-α and IL-8 expression.ConclusionsHigh Smad7 occurs in the inflamed mucosa of patients with CP, further supporting the pathogenic role of Smad7 in the gut.